Polarization-dependent strong and weak light-matter coupling in aligned perylene diimide thin films - Herrmann, Niklas; Hertzog, Manuel; Mischok, Andreas; Gather, Malte; Zaumseil, Jana (ACS applied optical materials, 2024)
Alignment of organic molecules in Fabry-Pérot microcavities can lead to increased light-matter coupling and polarization-dependent formation of exciton-polaritons. So far, only a few cases of polarization-dependent strong-coupling in aligned and birefringent organic systems have been investigated with different interpretations of the observed properties. Here, we create highly aligned thin films of the well-known perylene diimide fluorophore and n-type semiconductor PDIF-CN2 by zone-casting and integrate them in metal-clad Fabry-Pérot microcavities. The obtained thin-film polymorph exhibits both J-like and H-like aggregate behavior, depending on polarization. Using angle-resolved and polarization-selective reflectivity and photoluminescence measurements of the cavities, we analyze their response to different light polarization and propagation directions and find two orthogonally polarized optical systems with different coupling strengths. These two systems, one strongly coupled and one weakly coupled, are nearly independent of the incident light wavevector orientation and polarization due to the birefringent properties of the film. These contrasting cavity properties in combination with the good charge transport in PDIF-CN2 are highly interesting for polarization-selective photodetectors.